Visual intelligence : Microsoft tools and techniques for visualizing data - Stacey, Mark (Company founder); Salvatore, Joe (Business intelligence architect); Jorgensen, Adam (Indianapolis, Ind. : John Wiley & Sons, 2013)
Annotation. Go beyond design concepts and learn to build state-of-the-art visualizationsThe visualization experts at Microsoft's Pragmatic Works have created a full-color, step-by-step guide to building specific types of visualizations. The book thoroughly covers the Microsoft toolset for data analysis and visualization, including Excel, and explores best practices for choosing a data visualization design, selecting tools from the Microsoft stack, and building a dynamic data visualization from start to finish. You'll examine different types of visualizations, their strengths and weaknesses, and when to use each one. Data visualization tools unlock the stories within the data, enabling you to present it in a way that is useful for making business decisionsThis full-color guide introduces data visualization design concepts, then explains the various Microsoft tools used to store and display dataFeatures a detailed discussion of various classes of visualizations, their uses, and the appropriate tools for each Includes practical implementations of various visualizations and best practices for using themCovers out-of-the-box Microsoft tools, custom-developed illustrations and implementations, and code examplesVisual Intelligence: Microsoft Tools and Techniques for Visualizing Data arms you with best practices and the knowledge to choose and build dynamic data visualizations.
pt. I. Introduction to data visualization -- pt. II. Microsoft's toolset for visualizing data -- pt. III. Visual analytics in practice.
Keywords: Microsoft Windows (Computer file); Business intelligence -- Computer programs; Information visualization; Computer graphics; Business intelligence -- Computer programs; COMPUTERS -- Data Processing; Computer graphics; Computer literacy; Database design; Information visualization; Computer graphics; Business intelligence / Computer programs; Electronic books